Hunting Adeline - Carlton, H. D. (Cat & mouse duet, 2024)
Picking up where "Haunting Adeline" leaves off, with the point-of-view of the narrative alternating between hunter and hunted, Addie is kidnapped by the human trafficking ring that had pursued her in book 1, and must endure harrowing circumstances to survive and hopefully free herself from her captors.